Mentoring Local Tour Guides to Improve English Language Skills in Sade Hamlet, Nusa Tenggara Barat - Endang Sri Wahyuni; Siti Latifah; Ainul Yakin; Satria Rusdy Wijaya; Lalu Ahmad Zaki (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
The Community Service Program (PKM) in Sade Hamlet, Rembitan Village, NTB, was implemented to mitigate the negative impact of the